Compressive Strength Test on Calcium Hydroxide with Propolis Combination - Ira Widjiastuti; S. Setyabudi; M. Mudjiono; Erika Setyowati (Universitas Airlangga, 2019)
Background: Calcium hydroxide is a dental material used as a gold standard for pulp capping materials. However, calcium hydroxide has several weaknesses which cause many researchers to look for alternative ingredients that come from nature. Propolis in the field of dentistry has long been used because of its ability as an anti-inflammatory, anti-microbial, anti-fungal, and can cure scars. The combination of calcium hydroxide and propolis is proven to have good biocompatibility and anti-bacterial properties. One of the requirements of pulp capping material is to have sufficient compressive strength. Therefore, a research to test the compressive strength value of the combination of calcium hydroxide with propolis is needed. Purpose: To find out the difference in compressive strength of the combination of calcium hydroxide-propolis with a ratio of 1: 1, 1: 1.5, and 1: 2. Methods: The study used 4 treatment groups with each group consisting of 6 replications. Group 1 is a combination of calcium hydroxide-propolis with a ratio of 1: 1, group 2 with a ratio of 1: 1.5, group 3 with a ratio of 1: 2, and a positive control group using calcium hydroxide - sterile aquadest. Calcium hydroxide powder and propolis extract liquid is mixed according to comparison and printed on a cylindrical mold with the size of 4 mm x 6 mm. Then, the compressive strength was tested using an Autograph test instrument. Result: Compressive strength was smaller in group 3 compared to group 2, group 2 compared to group 1, and group 1 compared to the control group. Conclusion: In calcium hydroxide-propolis combination, the more propolis extract used in the combination the lower the compressive strength of the combination will be.